Comparison of safety and effectiveness between laparoscopic and open pancreatoduodenectomy: a systematic review and meta-analysis - Yin, Taoyuan; Qin, Tingting; Wei, Kongyuan; Shen, Ming; Zhang, Zhenxiong; Wen, Jingjing; Pan, Shutao; Guo, Xingjun; Zhu, Feng; Wang, Min; Zhang, Hang; Hilal, Mohammad Abu; et al. (International journal of surgery, 2022)
Background - Validity of the laparoscopic approach in pancreatic head lesion remains debatable. This study aims to compare the safety and effectiveness of laparoscopic pancreatoduodenectomy (LPD) and open pancreatoduodenectomy (OPD) and investigate the source of heterogeneity from surgeons’ and patients’ perspectives. - Method - We searched PubMed, Cochrane, Embase, and Web of Science for studies published before February 1, 2021. Of 6578 articles, 81 were full-text reviewed. The primary outcome was mortality. Three independent reviewers screened and extracted the data and resolved disagreements by consensus. Studies were evaluated for quality using ROB2.0 and ROBINS-I. According to different study designs, sensitivity and meta-regression analyses were conducted to explore the heterogeneity source. This meta-analyses was also conducted to explore the learning curve’s heterogeneity. This study was registered with PROSPERO, CRD42021234579. - Results - We analyzed 34 studies involving 46,729 patients (4705 LPD and 42,024 OPD). LPD was associated with lower (P = 0.025) in unmatched studies (P = 0.017). No differences in mortality existed in randomized controlled trials (P = 0.854) and matched studies (P = 0.726). Sensitivity analysis found no significant difference in mortality in elderly patients, patients with pancreatic cancer, and in high- and low-volume hospitals (all P > 0.05). In studies at the early period of LPD (<40 cases), higher mortality (P < 0.001) was found (all P < 0.05).LPD showed non-inferiority in length of stay, complications, and survival outcomes in all analyses. - Conclusion - In high-volume centers with adequate surgical experience, LPD in selected patients appears to be a valid alternative to LPD with comparable mortality, LOS, complications, and survival outcomes.